Machine Translation - Marileide Dias Esqueda (Trabalhos em Linguística Aplicada, 2021)
Considering the boost in technological development, and that machine translation has been widely used by both industry and academia, the main goal of this paper is to describe possibilities for the incorporation of a basic machine translation module in a Translation program at university level. The didactic proposal herein presented aims at providing Translation students ways of identifying general output results different modern machine translation systems have in common. Through a task-based teaching approach, students may assess machine translation strengths and weaknesses in order to make better use of this technology.